2012
DOI: 10.1080/03067319.2010.549339
|View full text |Cite
|
Sign up to set email alerts
|

Natural radionuclides and metals intake into soya, corn and lettuce grown on soil amended with phosphogypsum

Abstract: Phosphogypsum is a by-product of the phosphate fertilizer industry. It is produced by precipitation during wet process of phosphate rocks, thus posing serious problems with its utilization and safe disposal. In Brazil, three main industries are responsible for the production and storage of about 5.5 Â 10 6 tons per year. Phosphogypsum may contain trace metals and radionuclides of U and Th series. Since, in Brazil, phosphogypsum has been used for many years as soil amendment, it is important to know its availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
(28 reference statements)
4
4
0
1
Order By: Relevance
“…The radionuclides of the U and Th natural series are in equilibrium in the soils analyzed. The concentrations observed in the clay soil are approximately four times higher than the sandy soil; the results are in good agreement with literature values for Brazilian soils (Peres, 2007;Mazzilli et al, 2012). It can be observed that the radionuclides concentrations in the mixture soil þ PG are not statistically different from the concentration observed in the soils.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The radionuclides of the U and Th natural series are in equilibrium in the soils analyzed. The concentrations observed in the clay soil are approximately four times higher than the sandy soil; the results are in good agreement with literature values for Brazilian soils (Peres, 2007;Mazzilli et al, 2012). It can be observed that the radionuclides concentrations in the mixture soil þ PG are not statistically different from the concentration observed in the soils.…”
Section: Resultssupporting
confidence: 92%
“…The element selenium was not found in all the samples analysed. The results of the elements concentration are in accordance with literature values for soil from São Paulo State (Mazzilli et al, 2012).…”
Section: Resultssupporting
confidence: 88%
“…The 210 Po TF was greater when compared with the other radionuclides for all sample groups. For 210 Po, the TF value was comparable with that found by Mazzilli et al (2012) for sand soils with phosphogypsum application in soybean samples in Brazil. The few reports on the distribution of 210 Po and other radionuclides in plants (Tome et al, 2003;Mitchell et al, 2013) makes the comparison between the values reported here limited.…”
Section: Uptake Of Radionuclides By Soybean and Wheatsupporting
confidence: 77%
“…Some researchers in Brazil investigated the absorption of radionuclides by plants from soil (Vasconcellos et al, 1987;Santos et al, 1993Santos et al, , 2002Lauria et al, 1994;Mazzilli et al, 2012), but no investigation was performed in areas affected by coal mining. Radionuclide analysis in vegetables cropped near coal mining areas in southern Brazil, especially for those plants used for human consumption, could improve the radiological risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of natural radionuclides in the Brazilian phosphate mineral ores and their redistribution in products and by-products is well known (Mazzilli et al, 2000;Saueia & Mazzilli, 2006;Mazzilli et al, 2011). However, few data is available concerning the distribution of metals in the phosphate industry (Saueia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%